Une géographie du Brésil en 3 dimensions - François Moriconi-Ebrard (Confins)
This article explores the geopolitical role of elevation, this third but forgotten dimension of the of spatial modelization in geography. The model is here applied to the Brazilian process of settlement from the time of conquest to the contemporary era.The starting point is the “choreme” due to Hervé Théry which concludes the Atlas of Brazil (GIP Reclus, 1986) and which is a true reference in terms of organization of the national space of this country.The hypothesis is that the actors try to seize positional singularities and to control politically the trajectories that lead to them. The topography of Brazil is geometrically symbolized by a topographic dome that can be circumvented by the north (Amazon thalweg), the east (Paranean thalweg) and by the west (Atlantic littoral). The appropriation of the dome is made by circumvention movements (phase 1), then by ascending penetration pathways using the valley bottoms (phase 2), then, on the contrary, by top-down pathway following the interfluve peak lines (phase 3). We thus find a classical three-phase periodization of the Brazilian population and economic history (Pinheiro, 2007), each of which is characterized by privileged positions that can be assigned to topographic logics, and singular geopolitical trajectories that allow to control these positions.The relative importance of these three phases is measured using three simple variables: the central geocoordinates of the municipalities, the evolution of their population since 1872, under the constraint of the "elevation above the sea level" variable. This model allows to reconstruct by a theoritical reasoning the fundamental characteristics of the spatial structures of Brazil. It opposes among other things two societies : that of Littoral / Nordeste to that of the heights of the Interior, which is a political reality still current. This modeling also makes it possible to reconnect certain human and physical basic realities which found the unity of the geographical sciences.